Mendesain Bahan Ajar Bahasa Indonesia untuk Tujuan Akademis - Widjono Hs. (Lingua Cultura, 2008)
Article on how to design Indonesian language course material for academic purposes discusses some aspects necessary to be understood in designing the materials used by students at university level. Understanding of language essence, academic competence, appropriate course materials, and effective learning process covering the three stages of accountability model according to Moore, and the seven textuality criteria according to Rankema, is ablsolutely needed to be able to design good course materials. Article also includes a model structure of learning academic paragraph writing and academic essay.